2019
DOI: 10.1002/nafm.10353
|View full text |Cite
|
Sign up to set email alerts
|

An Importance–Satisfaction Analysis of Trout License Holders in Georgia

Abstract: As anglers become increasingly diverse, fisheries managers are challenged to find ways to satisfy users with divergent preferences while conserving a limited resource on a limited budget. With this management challenge in mind, this study combines previous angler specialization research with an importance-satisfaction analysis (ISA) to aid fisheries managers in better understanding users with divergent preferences. An ISA involves asking stakeholders to simultaneously evaluate the importance of salient attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The least specialized cluster reported a lack of fishing partners as a constraint often faced when attempting to trout fish in Georgia. A related study found this same least specialized group of anglers reported trout fishing attributes specifically related to catching trout (e.g., number of trout caught, size of trout caught, catching wild trout, catching stocked trout) as less important than attributes not related to catch, such as clean bathrooms and campgrounds at access points, habitat improvement initiatives, and distance to the trout stream from home (TenHarmsel et al 2019). Another potentially important factor for this least specialized group of anglers is the social aspect of trout fishing.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…The least specialized cluster reported a lack of fishing partners as a constraint often faced when attempting to trout fish in Georgia. A related study found this same least specialized group of anglers reported trout fishing attributes specifically related to catching trout (e.g., number of trout caught, size of trout caught, catching wild trout, catching stocked trout) as less important than attributes not related to catch, such as clean bathrooms and campgrounds at access points, habitat improvement initiatives, and distance to the trout stream from home (TenHarmsel et al 2019). Another potentially important factor for this least specialized group of anglers is the social aspect of trout fishing.…”
Section: Discussionmentioning
confidence: 95%
“…Contact information for resident trout anglers with a 2015 trout license was obtained from the GA DNR license database. Sample members ( n = 4,000) were selected from the GA DNR license database by proportionate random sampling based on license type (see TenHarmsel et al 2019 for more details on the proportionate random sampling procedure). The sample was comprised of both lifetime license holders and anglers who must repurchase their licenses every 1–3 years.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations